Eksistensi MUI Bukittinggi dalam Pembinaan Anak Jalanan - Rozalm, Salsabilla; Tyka, Tyka (Asian Journal of Islamic Studies and Da'wah, 2024)
This research is motivated by the role of the MUI towards street children in Bukittinggi City. The purpose of this research is to determine the role of the Bukittinggi MUI in developing street children. The method used in this research is qualitative, with data collection techniques through interviews, observation and documentation studies. The location of this research is in Bukittinggi City. In collecting data for this research, the key informants were the Bukittinggi City MUI, Social Service, Ministry of Religion, UPTD, and street children. The results of the research show that the Bukittinggi City MUI is active in carrying out research on the existence of the MUI in developing street children, namely that the Bukittinggi MUI plays a significant role in providing education and skills that help street children to improve their quality of life. The programs offered, such as religious learning and skills training, have had a visible positive impact in increasing children's self-confidence and motivation to achieve a better future. Children feel accepted and cared for by MUI administrators, who create a supportive environment for them. Even though the children face challenges, such as difficulty focusing and feeling inferior due to their background, they remain optimistic and hope to change their fate. Through the support provided by MUI, they have the hope of obtaining better jobs and contributing to society. In conclusion, the existence of MUI Bukittinggi in developing street children not only provides education and skills, but also changes the way children view themselves and their future.